An expert system based on Wavelet Neural Network-Adaptive Norm Entropy for scale invariant texture classification - Avci, Engin (Pergamon-Elsevier Science Ltd, 2007)
Nowadays, texture classification becomes more important, as the computational power increases. The most important hardness of texture image analysis in the past was the deficiency of enough tools to characterize variety scales of texture images effectively. Recently, multi-resolution analysis such as Gabor filters, wavelet decompositions provide very good multi-resolution analytical tools for different scales of texture analysis and classification. In this paper, a Wavelet Neural Network based on Adaptive Norm Entropy (WNN-ANE) expert system is used for increasing the effectiveness of the scale invariant feature extraction algorithm (Best Wavelet Statistical Features (WSF)-Wavelet Co-occurrence Features (WCF)). Efficiently of proposed method was proved using exhaustive experiments conducted with Brodatz texture images. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: expert systems; texture image; wavelet statistical features; wavelet co-occurrence features; feature extraction; texture classification